Akbar and the Jesuits : an account of the Jesuit missions to the court of Akbar - Du Jarric, Pierre, 1566-1617 (Broadway travellers, 2005)
First published in 1926.'These documents are full of intimate interest' Times Literary Supplement'A serious and intensely interesting piece of work' The GuardianThe Jesuit missionaries were some of the earliest Europeans to find their way into the Mogul empire in the sixteenth century. Spending more years at Akbar's court than others did months, and traversing his dominions from Lahore to Kabul, and from Kashmir to the Deccan, they undoubtedly sowed the seeds of British influence in the East.Reproducing, or summarizing the most valuable of the missionaries' l.